REVITALISASI KAWASAN KOTA LAMA SEMARANG: ANTARA HARAPAN DAN KENYATAAN - Sonaesti, Ceratomia; Purwanto, Edi (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2022)
Abstract: Semarang Old Town area has a row of historic buildings. Revitalization efforts have been made by the Government since 2017 to increase the attractiveness of the area in order to increase tourism potential in Semarang and to maintain the preservation of cultural heritage buildings. Currently, the condition of this area is getting better and more lively and attracts more visitors. However, so far there are various assumptions regarding of the Semarang Old City Area’s revitalization successness, so it is necessary to conduct a study to find out the problems that still exist to increase the successness of this area’s revitalization. This study was using a a comparative descriptive method. The evaluation results show that the revitalization of this area has not yet fully met the revitalization objectives, because although it has been able to improve its physical, economic and social qualities, it has not yet fully improved from a cultural perspective because there are still several problems, including street furniture, crowds concentrated in one area, volume of vehicles, infrastructure development, many unused buildings, vandalism and building facades differences. This is also not in accordance with the Government's vision of making this area a permanent list of